Perception of General British monophthongs : the case of Slovene students of English as a foreign language - Stopar, Andrej, lingvist (Array, 2019)
The paper presents an experimental study on the perception of the Gen-eral British monophthongs that was conducted in three stages in 2014–2018. The vowels observed are studied by (i) comparing the vowel sys-tems of General British and Slovene, and (ii) by conducting an experi-ment on their perception. The analysis focuses on the participants’ over-all performance, their most frequent misperceptions, and their progress over the course of one semester. The results indicate: that the previously observed production difficulties mirror perception difficulties; that the discriminative failures of FL vowels are not entirely predictable by com-paring vowel systems; that new sound contrasts are assimilated in differ-ent ways; and that the participants’ perception of foreign language pho-nemes can benefit from explicit instruction.